YTHDF1 gene inhibits epilepsy progression by epigenetic activation of PTEN gene - Mingxia Li; Junli Yang; Lixiang Gao (Heliyon)
Epilepsy is a common chronic neurological disorder with high prevalence that profoundly affects millions of people worldwide. Inflammatory dysregulation affects central nervous system disorders including epilepsy, and YTHDF1, the most common ''reader'' of m6A and m6A-binding protein, can attenuate the inflammatory response and activate PTEN, and here we aimed to investigate its effect on epilepsy through epigenetics. All mice were injected intraperitoneally with 12 mg/kg of sea manic acid to establish an epilepsy model, and the epileptic behaviors of the mice were classified into 6 grades; epileptic behaviors of grade 3 or above were defined as seizures, and consecutive epileptic seizures of more than 30 min were considered as successful modeling. Mouse behavior was examined using the Morris Water Maze tracking assay; inflammatory factors IL-6, TNF-α, and IL-1β were detected by qPCR/WB/ELISA; cell activity was analyzed by CCK-8; apoptotic markers were identified by immunofluorescence assay and Western blot analysis. YTHDF1 knockout mice have poor spatial memory capacity and sensitivity to external stimuli. Under the influence of YTHDF1, the neuroinflammation and nseuron death decreased. YTHDF1 works by repressing the production of pro-inflammatory cytokines and the activation of astrocytes. It was found that YTHDF1 epigenetically activates PTEN through m6A modification, activates glial cells and represses pro-inflammatory cytokines production and inhibits the development of epilepsy.